Adjunctive granisetron therapy in patients with sepsis or septic shock (GRANTISS): Study protocol for a randomized controlled trial. Issue 39 (September 2019) - Guan, Jianbin; Guo, Yuexun; Chang, Ping; Gan, Jianwei; Zhou, Jian; Wang, Hua; Cen, Zhongran; Tang, Ying; Liu, Zhanguo; Chen, Peng
Abstract: Introduction: The incidence, mortality, and treatment costs of sepsis are high and, thus, present a major challenge for critical care medicine. Our previous studies suggest that intestinal metabolite granisetron has a potential therapeutic effect on sepsis. Granisetron is a clinically widely used antiemetic, which is safe, inexpensive, and reliable. However, its value in the treatment of sepsis remains unclear. This study aims to explore the efficacy and safety of granisetron in the treatment of sepsis. Methods and analysis: A single-center, single-blind, randomized, controlled clinical trial will be conducted on 154 patients with sepsis. Patients who meet sepsis 3.0 diagnostic criteria, aged ≥18 and ⩽80 years, with PCT ≥ 2 ng/mL will be recruited. Patients will be randomized to receive intravenous granisetron 3 mg every 8 hours (n = 77) or an equal volume of normal saline (n = 77) for a treatment period of 4 days or to ICU discharge. The primary outcome is 28-day all-cause mortality. Secondary outcome measures include requirements for organ function support, changes of organ function, changes in infection biomarkers, changes in inflammatory and immune biomarkers, and the proportion of new organ failure. Adverse events and serious adverse events also will be observed closely. Ethics and dissemination: The study was approved by the Clinical Ethics Committee of Zhujiang Hospital of Southern Medical University (2018-ZZJHZX-009). The trial results will be disseminated at national and international conferences and through peer-reviewed journal. Trial registration: NCT03924518.URL: www.clinicaltrials.gov . Protocol date: 1 May 2019. version 2.1.